Pragmalinguistik Tuturan Guru Bahasa Indonesia SMP dalam Pembelajaran di Kelas - Septiana, Ika; Muhajir, Muhajir; Ripai, Ahmad (Universitas Muhammadiyah Magelang, 2026)
The importance of teacher communication in creating communicative, interactive, and responsive interactions during classroom learning with students. This certainly makes language in speech an important tool as a means of communication in conveying learning materials, giving instructions, directing, and motivating students during the learning process. The use of appropriate speech can increase student interaction and involvement during the learning process. Pragmalinguistics is a combination of two disciplines of pragmatics and linguistics. In communication activities, pragmalinguistics has an important role related to language politeness and sentence structures used in communication. The purpose of this article is to describe teacher speech acts in the process of learning Indonesian in the classroom. The research method uses a qualitative approach. Data collection was carried out through classroom observation. The study was conducted during Indonesian language learning for grade VII junior high school students. The subjects of this study were Indonesian language teachers and grade VII students of SMP Negeri 37 Semarang City. Data analysis was carried out by categorizing speech acts based on Lech's theory of locution, illocution, and perlocution. The research results show that the pragmalinguistics of Indonesian language teachers' speech in junior high school learning include several speech acts, including illocutionary acts to convey information, commands, and questions. Illocutionary acts are used to give orders, requests, or express emotions. Perlocutionary acts are used to influence students to take action. These three speech acts support effective learning interactions in the classroom.